Effects of Intensive Voice Treatment (The Lee Silverman Voice Treatment [LSVT LOUD]) in Subjects With Multiple Sclerosis: A Pilot Study - Baldanzi, Cinzia; Crispiatico, Valeria; Foresti, Sarah; Groppo, Elisabetta; Rovaris, Marco; Cattaneo, Davide; Vitali, Chiara (Journal of voice, 2022)
The rehabilitation of voice disorders is an unmet need in multiple sclerosis (MS). The Lee Silverman Voice Treatment (LSVT LOUD) is a well-documented and effective speech treatment, developed to treat voice disorders in Parkinson Disease. The purpose of the present study was to examine the viability of applying the LSVT LOUD to individuals with MS and verify short- and long-term improvements in acoustic and perceptual voice parameters. A single subject design was performed in a consecutive sample of 8 subjects with MS. The subjects’ voice was recorded with PRAAT software for 5 days at baseline during the 16  treatment sessions, and at follow-up (FU) 6/12 months later. PRAAT provided data on sustained /a/ (SPL/a/) voice intensity and maximum phonation time (MPT/a/) of sustained /a/, and on functional sentences voice intensity. In addition, self-assessment questionnaire Voice Handicap Index, the perceptual GIRBAS scale and intensity of monologue were collected at first day of baseline, post-treatment and at FU. In the treatment phase each subject received treatment according to LSVT LOUD protocol. Visual analysis calculated for daily acoustic variables was used to determine baseline stability and analyse changes following treatment. The Wilcoxon test was used to assess statistically significant differences between baseline and post treatment. All participants completed the LSVT LOUD programme; one participant dropped out at FU. Improvements in acoustic analysis were found: SPL/a/ improved on average (± standard deviation) 11.64 ± 4.19 dB with 7 subjects showing statistically significant improvement (P < 0.05); MPT/a/ improved on average 1.2 ± 1.53seconds, while intensity of functional sentences improved on average 8.11 ± 3.46  dB with 4 and 5 subjects showed statistically significant improvement, respectively. Intensity of monologue improved 14.90 ± 3.33 dB. Acoustic values are maintained or increased at FU respect to baseline. All subjects improved perceptual ratings at Voice Handicap Index and results were maintained at FU. These changes were associated with improvements on five parameters on the GIRBAS scale at post-treatment, however no further improvement were observed at FU. Intensive LSVT LOUD treatment is a viable approach to treat hypophonia in MS. LSVT LOUD improved both quantitative-instrumental and perceptive-subjective assessments. Randomised controlled trials are needed to provide a firm support on the effectiveness of LSVT LOUD in MS.